Impact of Standardized Patients on First Semester Nursing Students Self-Confidence, Satisfaction, and Communication in a Simulated Clinical Case - Kelly V. Johnson EdD, RN; Allison L. Scott DNP, APRN; Lisa Franks MSN, RN (SAGE Publishing, 2020)
Background Utilizing standardized patients (SPs) as a strategy to potentially improve beginning level nursing students' confidence, satisfaction, and communication after simulated clinical cases is an innovative approach in nursing education. Aim The aim of this study was to examine to what extent an SP affected first semester nursing students' self-confidence, satisfaction, and communication using a simulated clinical case. Methods First semester undergraduate students in a bachelors of nursing program at a large university in the South-Central region of the United States ( N  =   100), were randomly assigned to one of the two groups. Each group was assigned the same case using either an SP or high-fidelity manikin. Students completed postsurveys immediately following completion of the simulation. Student's self-confidence, satisfaction, and communication were measured using the National League for Nursing Student Satisfaction and Self-Confidence in Learning for Nursing Education Research and an SP/Faculty Communication Checklist. Results An independent sample t test comparing the two student groups on each of the outcome variables was conducted for each of the research questions. Students who completed the simulation with an SP, reported greater satisfaction, and improved communication. Student reflective comments were significantly more positive in the SP group. There was no statistical difference between the two groups in self-confidence. Conclusion Further research is needed to determine whether the use of SPs versus high-fidelity manikins in simulated cases results in increased self-confidence in beginning level nursing students. Student satisfaction and communication are key components for nursing student success. The impact of SPs and the effect on student outcomes could have long-term benefits for undergraduate nursing programs.